A Laboratory-Associated Outbreak of Cryptosporidiosis. (September 2015) - Philpott, Matthew S.; Fautin, Charlie H.; Bird, Karyn E.; O'Reilly, Kathy L.
An outbreak of cryptosporidiosis involving 10 primary cases, as well as several additional presumptive primary cases, occurred among third-year veterinary medical students in October 2011. The investigation revealed that the outbreak was associated with a laboratory exercise involving euthanized dairy calves that were naturally infected with Cryptosporidium parvum, and was exacerbated by inappropriate personal protective equipment (PPE), the unsuitable location of the laboratory, and the absence of appropriate hand hygiene. The lab location was such that students lacked an area where contaminated outer clothing could be removed safely, resulting in the potential for secondary spread. One additional case probably resulted from secondary spread. The institutional biosafety officer and the chair of the college occupational safety committee worked with teaching faculty and the Dean of the College of Veterinary Medicine and other stakeholders to create and implement a series of control measures to minimize the potential for future infections among students. Control measures included prescreening of donor calves and culling of infected animals, changing the location of the laboratory to a facility where suitable hand hygiene and sanitation are accessible, using more robust PPE, removing and laundering of protective clothing on location, and better training for students exposed to potential sources of zoonotic pathogens. Since implementation of these control measures, several cycles of instruction have been completed with no additional infections. This case study illustrates the need for university biosafety professionals to proactively assist academic faculty and students by providing guidance for instructional activities involving possible biohazards.